2018
DOI: 10.1002/lary.27637
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term sinonasal outcomes after endoscopic skull base surgery with nasoseptal flap reconstruction

Abstract: Objectives The utilization of the nasoseptal flap (NSF) in endoscopic anterior skull base surgery (EASB) has resulted in reduced rates of postoperative cerebrospinal fluid leak (CSF). The long‐term impact on sinonasal function after surgery remains incompletely defined. Methods A consecutive series of patients undergoing EASB with NSF and with at least 3 years follow‐up was prospectively evaluated. Patient demographics, pre‐ and postoperative Sino‐nasal Outcome Test‐22 (SNOT‐22) scores, Lund‐Mackay scores (LMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 41 publications
2
26
0
Order By: Relevance
“…9 Accordingly, Riley et al published a prospective study questioning the long-term impact of the nasoseptal flap on the sinonasal function. 13 In fact, both the postoperative 22-item Sino-nasal Outcome Test-22 (SNOT-22) questionnaire 14 and the radiologic Lund-Mackay score (LMS) 15 showed a significant worsening, indicating a deterioration in function following anterior skull base surgery with nasoseptal flap. 13 Several authors more recently proposed other pedicled flap to repair ASBs even though long-term follow-up studies have not been published at present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Accordingly, Riley et al published a prospective study questioning the long-term impact of the nasoseptal flap on the sinonasal function. 13 In fact, both the postoperative 22-item Sino-nasal Outcome Test-22 (SNOT-22) questionnaire 14 and the radiologic Lund-Mackay score (LMS) 15 showed a significant worsening, indicating a deterioration in function following anterior skull base surgery with nasoseptal flap. 13 Several authors more recently proposed other pedicled flap to repair ASBs even though long-term follow-up studies have not been published at present.…”
Section: Discussionmentioning
confidence: 99%
“…13 In fact, both the postoperative 22-item Sino-nasal Outcome Test-22 (SNOT-22) questionnaire 14 and the radiologic Lund-Mackay score (LMS) 15 showed a significant worsening, indicating a deterioration in function following anterior skull base surgery with nasoseptal flap. 13 Several authors more recently proposed other pedicled flap to repair ASBs even though long-term follow-up studies have not been published at present. [16][17][18][19] The majority of the authors agree with the use of composite osteomucosal or chondromucosal grafts for defects bigger than 3 to 4 cm.…”
Section: Discussionmentioning
confidence: 99%
“…1,17,6 NSF success rates range from 70% to 100% in single institution studies, with most reporting success rates of 90% or higher. 1,21,22,[38][39][40] Other NSF variants Successful use of bilateral NSFs, termed the "Janus flap," has been reported for defects that may not be adequately repaired by a single NSF. 43,45 Single NSFs can also be enlarged by moving the inferior incision laterally to include mucosa from the inferior turbinate or even the entire lateral wall.…”
Section: Nsf Outcomesmentioning
confidence: 99%
“…The absence of postoperative CSF leaks is generally considered to be the primary measure of success for reconstruction of skull base defects 1,17,6 . NSF success rates range from 70% to 100% in single institution studies, with most reporting success rates of 90% or higher 1,21,22,38‐40 . Additional NSF complications and their prevalence were assessed in a 2018 systematic review by Lavinge et al: flap necrosis (4 studies; [0%‐1.3%]), mucocele formation (5 studies; [0%‐3.6%]), septal perforation (6 studies; [0%‐14.4%]), and nasal dorsum collapse (2 studies, [0.7%‐5.8%]).…”
Section: Intranasal Vascular Pedicled Flapsmentioning
confidence: 99%
“…6,7 In a prospective study examining patients undergoing ESBS with NSF reconstruction, there was a significant increase in the 22-item Sino-Nasal Outcome Test nasal symptom subdomain as well as Lund–Mackay scores postoperatively. 8 Recent studies have shown that skull base defects that are small in size with a low-flow CSF leak can be reconstructed with a wide variety of multilayered (or even monolayered) avascular free grafts or biosynthetic materials with high success rates and limited morbidity. 3,9 In the setting of routine transspehnoidal surgery, where the risk of a high-flow CSF leak is low, the upfront harvest of the NSF per routine, could lead to an unnecessary flap with its attendant morbidity.…”
Section: Introductionmentioning
confidence: 99%